A Comparative Analysis of Social Development in Preschool Children of Working and Non-Working Mothers - Fatmawati, Fatmawati; Sari, Dian vita; Junaedy , Junaedy; Damayanti, Siti; Ardilla, Arista (Babali Publisher, 2024)
Background: Children's social development affects how they socialize with their surrounding environment, where some children have difficulty socializing and adjusting to the environment. The purpose of this study was to compare the social development of preschool-age children in working mothers and non-working mothers.Methods: This study used analytical observations with a cross-sectional design conducted by 113 mothers with preschool children aged 4-6. Data was collected using the DDST II questionnaire sheet specifically for aspects of personal social development. Results: The respondents were 20-35 years old (79.6%), almost half of the children were four years old (40.7%), and also half of the children were female (64.6%). Next, half of the mothers were working (75.3%), the nuclear family type (61.9%), and the social development of preschool children were mostly in the caution category, as much as 47.8%. There was a difference in the social development of children in working mothers and non-working mothers (p-value<0.05). Conclusion: It is expected that working mothers can manage their time, guide and supervise the development of their children, and provide independent trust and freedom to children so that they are not dependent on their parents to carry out age-appropriate developmental tasks.